Emptiness - Ceriani, Giulia (E|C, 2021)
That the emptiness is the matrix of any possible sense, the white space where the oppositions live, the necessary polarity of each conceptual fullness, it’s too easy to say. What’s different, instead, is to mark when emptiness overlaps its own paradoxical presence to what we know as density’s hyperboles, suddenly virtual: what does it happen if town abruptly stops to be an agglomerate of humanities crowding their proximity of economic and existential reasons, to become an ellipse, an implicit, a “tabula rasa” asking to re-think again its meaning? What does it happen if fullness is inside the houses and behind the walls? what is the sense of communication routes, meeting points, parks and squares, if their functions are overturned and become rejecting forces instead of aggregating? What the communicational strategies will be, how and if the media will represent the presence subtraction: over-investing it of digital representations, virtually erasing it thanks to simulacra and holograms, either, finally, returning the point of view that decides what is full and what is empty?